Cross-Border Provisional and Protective Measures for Preserving of Physician’s Funds Subject to a Liability Claim in the EU - Urška Kupec (Medicine, Law & Society, 2022)
Patients frequently opt for medical treatment outside the public health system. This means that the patient enters into a contract with an individual physician, which commits the physician to perform a medical procedure for the patient, and the patient undertakes to pay for this procedure. If the physician does not act with due diligence or does not achieve an outcome that they have explicitly committed to reach, a situation may arise where the patient has a monetary claim against the physician. If the physician does not repay the claim voluntarily, the patient has certain options available to ensure that their claim is forcibly repaid. In this paper, we deal with the position of the +patient as a creditor who does not yet have an enforceable title in relation to the physician and the debtor, and with a patient who already has such an enforceable title. The field of study is limited to the situation when Slovenian law applies for decision on the responsibility of a physician and patient wants to claim the funds that the physician has in bank accounts in the European Union.